Scriptures, Materiality, and the Digital Turn: The Iconicity of Sacred Texts in a Liminal Age. Issue 1 (24th June 2019) - Anderson, Bradford
Abstract : The "digital turn" witnessed over the past several decades has had a significant impact on the use of sacred texts, although the full extent of these developments is far from settled. This essay explores some of the social and cultural dynamics involved in converting or translating scriptures to digital formats, issues which take on heightened significance because of the sacred status of these texts in their respective traditions. Drawing on the notion of diverse functional dimensions of scriptures, this study highlights the complex way in which the use of sacred texts in Judaism, Christianity, and Islam is being affected by the digital turn. Specific focus is placed on the iconic role of scriptures, an aspect often bound up with issues of materiality. I conclude with some theoretical reflections that build on Jonathan Westin's "vocabulary of limitations, " which itself draws on the sociology of translation, to suggest that the material dimensions of scriptures in this liminal age highlights the role of these texts as objects which both embody and contribute to social and cultural values. These comparative perspectives offer suggestive possibilities for reflection on such material texts as "sacred beings."